2014
DOI: 10.1016/j.icarus.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and characterization of small-scale aeolian structures on Mars: An example from the MSL landing site in Gale Crater

Abstract: A new set of methodologies, which allow a simple and fast mapping and characterization of small-scale aeolian structures on Mars is introduced in this work. We follow an object-based approach in which the bedform crestlines are automatically mapped and characterized.From the methodology validation, we conclude that the quality of the obtained results is comparable with human-produced photointerpretations. We show that the accuracy associated with the measurement of mean trends from the automatically mapped pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…S4). It was shown that, in places, the wavelength of the large martian ripples may weakly increase or decrease upslope due to local variations in grain size or wind speed (57), although no consistent increase in height and wavelength upslope is observed, contrary to terrestrial compound dunes (43). Thus, the large martian ripples are distinct from compound dunes.…”
Section: S15 Additional Evidence In Favor Of the Wind-drag Hypothesismentioning
confidence: 99%
“…S4). It was shown that, in places, the wavelength of the large martian ripples may weakly increase or decrease upslope due to local variations in grain size or wind speed (57), although no consistent increase in height and wavelength upslope is observed, contrary to terrestrial compound dunes (43). Thus, the large martian ripples are distinct from compound dunes.…”
Section: S15 Additional Evidence In Favor Of the Wind-drag Hypothesismentioning
confidence: 99%
“…The COSI-Corr displacement maps are further improved by removing jitter artifacts ( Figure S2). We then used the Object-based Ripple Analysis technique [Vaz and Silvestro, 2014] to characterize the directional distribution of the LRs, evaluate their spatial distribution and correlate bed form pattern characteristics with migration rates and morphometric settings [Vaz and Silvestro, 2014;Vaz et al, 2015] ( Figure S3).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Yizhaq et al (2014) analyzed sand ripples at Eagle crater imaged by the Opportunity rover, and by coupling a numerical model for saltation with a dynamic ripple model, they conclude that the fine-grained ripples developed below the fluid threshold, consistent with the presence of substantial hysteresis in martian saltation. Finally, Vaz and Silvestro (2014) use a new set of analysis tools to characterize small-scale aeolian structures in the vicinity of the Curiosity landing site in Gale crater.…”
Section: Marsmentioning
confidence: 99%